Membentengi Pemuda Gereja dari Ajaran Guru Palsu Melalui Pemahaman 2 Petrus 3:3 - Santy Sahartian (Sekolah Tinggi Teologi Berita Hidup, 2021)
Based on 2 Peter 3: 3 latter-day life is the appearance of mockers called false teachers carrying false teachings, namely denying Jesus as a savior, turning the day of the Lord or the day of the second coming of Jesus, and rejecting the Word of God. The lives of these false teachers only follow the passions. Adultery, obscene, all of it to blaspheme the glory of God. To fortify youth in dealing with heresies and living according to lust is to provide proper teaching and formation on the knowledge of Christ in 2 Peter 1: 5-7. The growth of true faith, namely to the faith of virtue, to the virtue of knowledge, to the knowledge of self-mastery, to the mastery of perseverance, to the perseverance of godliness, to the piety of love for you, to your love for all people. Where this love does not demand reciprocity, this love is the love that is willing to sacrifice for the people it loves. With the right knowledge of Jesus, it will be difficult for young people to influence teachings that are not true.Kehidupan zaman akhir berdasar 2 Petrus 3:3 adalah tampilnya pengejek-pengejek yang di sebut guru palsu membawa ajaran sesat, yaitu menyangkal Yesus sebagai juruselamat, memutarbalikan hari Tuhan atau hari kedatangan Yesus yang kedua kalinya, dan menolak Firman Allah. Kehidupan guru-guru palsu ini hanya mengikuti hawa nafsu. Nafsu zinah, cabul, semuanya itu kepada menghujat kemuliaan Allah. Untuk membentengi pemuda dalam menghadapi ajaran-ajaran sesat dan kehidupan menuruti hawa nafsu adalah dengan memberi pengajaran dan pembinaan yang tepat tentang pengenalan akan Kristus dalam 2 Petrus 1:5-7. Adanya pertumbuhan iman yang benar, yaitu kepada iman kebajikan, kepada kebajikan pengetahuan, kepada pengetahuan penguasaan diri, kepada penguasaan diri ketekunan, kepada ketekunan kesalehan, kepada kesalehan kasih akan saudara, kepada kasih saudara kasih semua orang. Di mana kasih ini tidak menuntut balasan, kasih ini adalah kasih rela berkorban bagi sesama yang dikasihinya. Dengan pengenalan yang benar akan Yesus , maka pemuda akan sulit di pengaruhi ajaran yang tidak benar.